Rancang Bangun Aplikasi Penjadwalan Produksi Pada PT Goldfindo Intikayu Pratama - Saputro, Andri; Sudarmaningtyas, Pantjawati; Setyawan, Henry Bambang (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Abstract: PT Goldfindo Intikayu Pratama is a company who works in furniture field. The company’s production is based on the customer orders. The average of the company’s transaction reaches about 3000 products, yet 31% of them delayed. It is caused by several things, which are the absence of scheduling method, the machine’s functions are not optimized yet by the company, and also order data recording with production scheduling are not integrate yet. This research results an application that can compare four methods of scheduling. The four methods are EDD, FCFS, SPT and LPT. The comparison of methods is aimed to get the best method that will be used by the company for scheduling. It requires some stages to make the application, the first is requirements analysis, system design, implementation, and the last are integration and testing. From this research, its result is about 96% which means that the application is feasible to use, and the user trial results are about 91% which means that this application can be accepted by the company.